Macroeconomic Shocks and Market Persistence: A VECM Approach to the Indonesian Financial Sector - Thomas Sumarsan Goh; Erika Erika; Henry Henry; Albert Albert (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Research Originality: This study offers fresh insights by analyzing how inflation, exchange rates, and economic growth affect Indonesia’s IDX Finance sector, addressing a key gap in understanding the market's internal dynamics. Research Objectives: This study quantifies the impact of inflation, exchange rates, and economic growth on the Indonesian IDX Finance sector. Research Method: This study uses 62 monthly observations and a VECM to analyze short- and long-run relationships among variables. Empirical Results: Long-run VECM estimates reveal that the Consumer Price Index (CPI) and Exchange Rate (ER) exert significant positive pressures on IDXFINANCE, suggesting that moderate inflationary environments often catalyze credit expansion and heightened demand for financial intermediation. Conversely, Economic Growth (EG) exhibits a statistically negligible long-term impact. Implications: The findings indicate that IDX Finance is largely driven by its own past dynamics rather than by external macroeconomic shocks. As a result, internal market trends provide more reliable short-term predictions than traditional economic indicators, especially when the sector’s persistence is taken into account. JEL Classification: C5, E31, F31